“Women, Gender, and Financial Inclusion” - Tinuade A. Ojo (Digital Policy Studies)
Much of the institutions that form part of governing structures in African countries reflect gendered perspectives of notions such as freedom and development, thus resulting in a skewed perspective on the development of a country. African women often play second fiddle in matters such as redress, redistribution, and financial inclusion. There is a need to ask why and how this can be remedied through policy transformation and implementation.